From "Black Rice" to "Brown": Rethinking the History of Risiculture in the Seventeenth- and Eighteenth-Century Atlantic. - HAWTHORNE, WALTER (American Historical Review, 2010)
The article presents discussion concerning the "black rice thesis" promoted by some transatlantic historians and addressed in the journal's previous article "Agency and Diaspora in Atlantic History," by David Eltis, Philip Morgan, and David Richardson, originally printed in the December 2007 issue. The author challenges both the black rice thesis in general as well as the specific criticism offered in the original article, noting flaws within the methodology of both studies. Comments are given discussing the nature of historical "evidence." It is alternatively suggested that a moderate reinterpretation of the thesis be taken up, where the African and European colonial contributions to the growth of rice culture are both incorporated into the larger themes of Atlantic studies.